Lutetium oxide yttrium lutetium silicate mixed crystal and preparation method thereof
By using lutetium oxide yttrium lutetium silicate mixed crystal and adding specific elements to optimize its composition ratio, the performance requirements of fully digital PET for LYSO:Ce crystal have been improved, achieving higher density, light yield and faster attenuation. time.
Patent Information
- Application Number
- CN202411475039.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-21
AI Technical Summary
The prior art cannot meet the higher requirements of the full digital PET for the density, optical yield, energy resolution and attenuation time of LYSO:Ce crystals.
The mixed crystal of the oxidation sagnicate is used, and its molecular formula is (LU2O3) x: CE2Y: LU2 (1-Y-Z) -e2zmasio5. By adding at least one element in CA, MG, IN, SC, or AL The ratio of Z and A to improve the performance of the crystal.
The density, optical production, energy resolution, and faster attenuation time than existing LYSO: CE crystals, and faster attenuation time, meet the performance requirements of all -digital PET.
Smart Images

Figure CN119332343A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present invention relate to the field of scintillation crystals, and in particular to a lutetium oxide-yttrium silicate-lutetium mixed crystal and a preparation method thereof. Background Art
[0002] Ce:LYSO, a scintillating crystal commonly used in PET, has a high density (7.16 g / cm 3 ), high light yield (38000photons / MeV), short decay time (~40ns), fast response, high energy resolution (<10%) and other excellent characteristics meet the above requirements. Existing clinical PET instruments use LYSO:Ce crystals, which have better performance.
[0003] Domestic fully digital PET DigitMI9, United Imaging uEXPLORER and other clinical PET instruments use performance-optimized LYSO:Ce scintillation crystals, achieving time resolutions of 249ps and 430ps respectively. In the cutting-edge research of new PET detectors, multiple research organizations have reported that using LFS (modified LSO) with a size of 3mm×3mm×15mm can achieve a time resolution of 148ps; using 0.4% Ca-doped LSO:Ce with a size of 2mm×2mm×20mm can achieve a time resolution of (140±5)ps; using LGSO:Ce with a size of 2.9mm×2.9mm×20mm can achieve a time resolution of (122±4)ps.
[0004] In order to meet the material requirements of the increasingly developed all-digital PET, it is necessary to use scintillation materials that have higher density, faster decay time and other excellent scintillation properties than the LYSO:Ce crystals used on PET in the past, and can provide faster time resolution. Summary of the invention
[0005] The purpose of the embodiments of the present invention is to provide a lutetium oxide-yttrium silicate-lutetium mixed crystal with greater density, higher light yield, energy resolution and faster decay time.
[0006] In order to achieve the above object, the embodiment of the present invention designs a lutetium oxide yttrium silicate lutetium mixed crystal, comprising:
[0007] Its molecular formula is (Lu2O3) x :Ce 2y :Lu 2(1-y-z)-a Y 2z M a SiO5;
[0008] Wherein x=0.5%-20%, y=0.05%-2%, z=0.05%-20%, a=0.02%-0.6%.
[0009] Further, in the lutetium oxide yttrium silicate lutetium mixed crystal of the present invention, the Lu2O3: (Ce 2y :Lu 2(1-y-z)- a Y 2z M a SiO5)=x:1; the x value is 0.5%-20%.
[0010] Furthermore, in the lutetium oxide yttrium silicate lutetium mixed crystal of the present invention, the x value is more preferably 0.1%-5%.
[0011] Further, in the lutetium oxide yttrium silicate lutetium mixed crystal of the present invention, the Ce 2y :Lu 2(1-y-z)- a Y 2z M a The y value in SiO5 is 0.05%-2%.
[0012] Furthermore, in the lutetium oxide yttrium silicate lutetium mixed crystal of the present invention, the optimal value of y is 0.1%-0.5%.
[0013] Further, in the lutetium oxide yttrium silicate lutetium mixed crystal of the present invention, the Ce 2y :Lu 2(1-y-z)- a Y 2z M a The z value in SiO5 is 0.05%-20%.
[0014] Furthermore, in the lutetium oxide yttrium silicate lutetium mixed crystal of the present invention, the optimal value of z is 2%-10%.
[0015] Furthermore, in the lutetium oxide yttrium lutetium silicate mixed crystal described in the present invention, M is a combination of at least one or more of Ca, Mg, In, Sc, and Al.
[0016] Furthermore, in the lutetium oxide yttrium silicate lutetium mixed crystal of the present invention, the a value is 0.02%-0.6%.
[0017] In the present invention, a method for preparing the lutetium oxide yttrium silicate lutetium mixed crystal is also provided, comprising the following steps:
[0018] Step S10: taking dried lutetium oxide, yttrium oxide, cerium oxide, silicon dioxide and additives containing at least one or more of Ca, Mg, In, Sc or Al, mixing them evenly in the above proportions, pressing them into a cake shape, and pre-sintering them; obtaining a sintered block material and entering step S20;
[0019] Step S20: Load the sintered block material in step S10 into an iridium crucible, and then load it into a pulling furnace; proceed to step S30;
[0020] Step S30: After the seed crystal is installed on the lifting rod, the furnace is sealed and evacuated, and then filled with inert gas, the temperature is increased to melt the sintered block, and the temperature is maintained at a constant temperature, and then step S40 is entered;
[0021] Step S40: using a seed crystal to seed the crystal, and using a Czochralski growth process to control the pulling speed and crystal rotation speed; after the crystal growth is completed, slowly cooling down and taking out the crystal.
[0022] Further, in the method for preparing the lutetium oxide yttrium silicate lutetium mixed crystal of the present invention, the seed crystal in step S40 is lutetium oxide and Ce. 2y :Lu 2(1-y-z)-a Y 2z M a Seed crystals made from mixed crystals of SiO5.
[0023] Further, in the method for preparing the lutetium oxide yttrium silicate lutetium mixed crystal of the present invention, the step S10 is carried out according to the molar ratio of Lu2O3:Ce 2y :Lu 2(1-y-z)-a Y 2z M a SiO5, weigh dry raw materials with a purity higher than 99.99%, mix them evenly, and in the step S10, press the evenly mixed raw materials into cylindrical cakes under a pressure of 100 MPa; pre-sinter them at a temperature of 1450° C. for 12 hours;
[0024] After the seed crystal is installed on the lifting rod in step S30, the furnace is sealed and evacuated to 6×10 -3 After Pa, high-purity argon gas is filled in;
[0025] In step S40, lutetium oxide and Ce are used. 2y :Lu 2(1-y-z)-a Y 2z M a SiO5 mixed crystal seed inoculation, control the pulling speed to 0.01-5 mm / hour, and the crystal rotation speed to 3-20 rpm.
[0026] Compared with the prior art, the embodiment of the present invention adopts a lutetium oxide yttrium silicate lutetium mixed crystal, whose molecular formula is (Lu2O3)x :Ce 2y :Lu 2(1-y-z)-a Y 2z M a SiO5; wherein x = 0.5% - 20%, y = 0.05% - 2%, z = 0.05% - 20%, a = 0.02% - 0.6%. By adding at least one element of Ca, Mg, In, Sc or Al, the lutetium oxide yttrium silicate lutetium mixed crystal has a higher density, higher light yield, higher energy resolution and faster decay time than the LYSO in the prior art. The technical problem that the prior art cannot meet the requirements of the current full digital PET for LYSO: Ce is solved. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the preparation method of the present invention. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the following will be described in detail with reference to the accompanying drawings. However, it will be appreciated by those skilled in the art that in the various embodiments of the present invention, many technical details are provided in order to enable the reader to better understand the present application. However, even without these technical details and various changes and modifications based on the following embodiments, the technical scheme claimed for protection in the claims of the present application can be implemented.
[0029] The first embodiment of the present invention relates to a lutetium oxide-yttrium silicate-lutetium mixed crystal, comprising:
[0030] Its molecular formula is (Lu2O3) x :Ce 2y :Lu 2(1-y-z)-a Y 2z M a SiO5;
[0031] Wherein x=0.5%-20%, y=0.05%-2%, z=0.05%-20%, a=0.02%-0.6%.
[0032] The first half of the present invention (Lu2O3) x is lutetium oxide, the latter part is Ce 2y :Lu 2(1-y-z)-a Y 2z M aSiO5 is commonly referred to as doped LYSO:Ce. The lutetium oxide and yttrium lutetium silicate mixed crystal disclosed in the present invention is different from the traditional LYSO:Ce crystal in that the traditional LYSO:Ce crystal constraint ratio (Lu+Y):Si=2:1, or after adding other metal ions, the total molar number of metal ions other than silicon in the system is 2:1 to silicon, while in the present invention, lutetium oxide is additionally added to prepare the mixed crystal, which has a greater density and excellent scintillation performance; the lutetium oxide yttrium lutetium silicate mixed crystal, which is prepared by adding at least one or more of Ca, Mg, In, Sc or Al, has a greater density, higher light yield, energy resolution and faster decay time than the LYSO in the prior art. The technical problem in the prior art that the performance requirements of the existing scintillation materials for the fully digital PET cannot be met is solved.
[0033] In order to achieve the above technical effects, in the lutetium oxide yttrium silicate lutetium mixed crystal of this embodiment, (Lu2O3) x :Ce 2y :Lu 2(1-y-z)-a Y 2z M a SiO5; x value is 0.5%-20%; the preferred x value is 0.1%-5%.
[0034] In the lutetium oxide yttrium silicate mixed crystal of this embodiment; Ce 2y :Lu 2(1-y-z)-a Y 2z M a The y value in SiO5 is 0.05%-2%; the preferred y value is 0.1%-0.5%.
[0035] In the lutetium oxide yttrium silicate mixed crystal of this embodiment; Ce 2y :Lu 2(1-y-z)-a Y 2z M a The z value in SiO5 is 0.05%-20%; the preferred z value is 2%-10%.
[0036] In the lutetium oxide yttrium silicate mixed crystal of this embodiment; Ce 2y :Lu 2(1-y-z)-a Y 2z M a The a value in SiO5 is 0.02%-0.6%.
[0037] In a second embodiment of the present invention, a method for preparing the lutetium oxide-yttrium silicate mixed crystal is also provided, such as Figure 1 As shown, including the following steps:
[0038] Step S10: taking dried lutetium oxide, yttrium oxide, cerium oxide, silicon dioxide and additives, mixing them evenly according to the mixing ratio, pressing them into a cake shape, and pre-sintering them; the obtained sintered block material enters step S20;
[0039] Step S20: Load the sintered block material in step S10 into an iridium crucible, and then load it into a pulling furnace; proceed to step S30;
[0040] Step S30: After the seed crystal is installed on the lifting rod, the furnace is sealed and evacuated, and then filled with inert gas, the temperature is increased to melt the sintered block, and the temperature is maintained at a constant temperature, and then step S40 is entered;
[0041] Step S40: using a seed crystal to seed the crystal, and using a Czochralski growth process to control the pulling speed and crystal rotation speed; after the crystal growth is completed, slowly cooling down and taking out the crystal.
[0042] In order to achieve the above steps, the preparation method of the lutetium oxide yttrium silicate lutetium mixed crystal in the present invention is as follows: Figure 1 As shown, the seed crystal in step S40 is lutetium oxide and Ce 2y :Lu 2(1-y-z)-a Y 2z M a Seed crystals made from mixed crystals of SiO5.
[0043] In order to achieve the above steps, the preparation method of the lutetium oxide yttrium silicate lutetium mixed crystal in the present invention is as follows: Figure 1 As shown, the step S10 is based on the molar ratio (Lu2O3) x :Ce 2y :Lu 2(1-y-z)-a Y 2z M a SiO5, weigh lutetium oxide, yttrium oxide, cerium oxide, silicon dioxide and additives with a purity higher than 99.99%, mix them evenly, in the step S10, press the lutetium oxide and yttrium lutetium silicate mixed crystals into a cylindrical cake under a pressure of 100 MPa; pre-sinter at a temperature of 1450° C. for 12 hours;
[0044] After the seed crystal is installed on the lifting rod in step S30, the furnace is sealed and evacuated to 6×10 -3 After Pa, high-purity argon gas is filled in;
[0045] In step S40, lutetium oxide and Ce are used. 2y :Lu 2(1-y-z)-a Y 2z M a SiO5 mixed crystal seed inoculation, control the pulling speed to 0.01-5 mm / hour, and the crystal rotation speed to 3-20 rpm.
[0046] According to the above embodiments, the present invention also provides the following embodiments:
[0047] In the following examples, Ce 2y :Lu 2(1-y-z)-a Y 2z M a SiO5 selects the best ratio Ce 0.004 Lu 1.986- a Y 0.01 M a SiO5
[0048] Embodiment 1:
[0049] According to the molar ratio of Lu2O3:(Ce 0.004 Lu 1.986-a Y 0.01 M a SiO5) = 0.05:1 Weigh the dry raw material with a purity of 99.99%, add 0.2 mol% CaO additive, mix well, press into Φ80 mm cake under a pressure of 100 MPa, pre-sinter at 1500 ° C for 12 hours; put the sintered block into the Φ100×100 mm 3 The iridium crucible is loaded into the pulling furnace, the seed crystal is installed on the pulling rod, and then the furnace is sealed and vacuumed to or better than 6×10 -3 Pa, then high-purity argon was filled in, and the temperature was raised to melt the material; after the material was completely melted into a melt, the temperature was kept constant for 2 hours; the Czochralski growth process was adopted, the pulling speed was 2 mm / hour, and the crystal speed was 12 rpm. After the crystal growth was completed, the temperature was slowly lowered for 40 hours and the crystal was taken out, and a Φ50×80mm 3 Transparent and complete lutetium oxide yttrium silicate lutetium mixed crystal.
[0050] Embodiment 2:
[0051] According to the molar ratio of Lu2O3:(Ce 0.004 Lu 1.986-a Y 0.01 M a SiO5) = 0.1:1 Weigh the dry raw material with a purity of 99.99%, add 0.4 mol% (CaO + Al2O3) additives, mix well, press into Φ120mm cake under a pressure of 100MPa, pre-sinter at 1500℃ for 12 hours; put the sintered block into Φ150×100mm 3 The iridium crucible is loaded into the pulling furnace, the seed crystal is installed on the pulling rod, and then the furnace is sealed and vacuumed to or better than 6×10 -3Pa), then filled with high-purity argon, heated to melt the material; after the material was completely melted into a melt, the temperature was kept constant for 2 hours; the pulling method was used for growth, the pulling speed was 2 mm / hour, and the crystal speed was 8 rpm. After the crystal growth was completed, the temperature was slowly lowered for 60 hours and the crystal was taken out, and a Φ100×60mm 3 Transparent and complete lutetium oxide yttrium silicate lutetium mixed crystal.
[0052] Embodiment 3:
[0053] According to the molar ratio of Lu2O3:(Ce 0.004 Lu 1.986-a Y 0.01 M a SiO5) = 0.2:1 Weigh the dry raw material with a purity of 99.99%, add 0.6 mol% (CaO + Al2O3 + MgO) additives, mix well, press into Φ120mm cake under a pressure of 100MPa, pre-sinter at 1500℃ for 12 hours; put the sintered block into Φ150×100mm 3 The iridium crucible is loaded into the pulling furnace, the seed crystal is installed on the pulling rod, and then the furnace is sealed and vacuumed to or better than 6×10 -3 Pa, then high-purity argon was filled in, and the temperature was raised to melt the material; after the material was completely melted into a melt, the temperature was kept constant for 2 hours; the Czochralski growth process was adopted, the pulling speed was 0.8 mm / hour, and the crystal speed was 6 rpm. After the crystal growth was completed, the temperature was slowly lowered for 60 hours and the crystal was taken out, and a Φ100×60mm 3 Transparent and complete lutetium oxide yttrium silicate lutetium mixed crystal.
[0054] The lutetium oxide yttrium lutetium silicate mixed crystals prepared according to the preparation method of the above embodiment are compared with the existing crystals, and the specific structure is as follows:
[0055]
[0056] According to the above-mentioned embodiments, the lutetium oxide yttrium silicate lutetium mixed crystal has better scintillation performance and the best comprehensive scintillation performance, especially embodiment 2 has achieved the best data.
[0057] Those skilled in the art will appreciate that the above-mentioned embodiments are specific examples for implementing the present invention, and in actual applications, various changes may be made thereto in form and detail without departing from the spirit and scope of the present invention.
Claims
1. A lutetium oxide yttrium silicate lutetium mixed crystal, characterized in that: Its molecular formula is (Lu2O3) x :Ce 2y :Lu 2(1-y-z)-a Y 2z M a SiO5.
2. The lutetium oxide yttrium silicate lutetium mixed crystal according to claim 1, characterized in that: The (Lu2O3): (Ce 2y :Lu 2(1-y-z)-a Y 2z M a SiO5)=x:1; the x value is 0.5%-20%.
3. The lutetium oxide yttrium silicate lutetium mixed crystal according to claim 1, characterized in that: The y value is 0.05%-2%.
4. The lutetium oxide yttrium silicate lutetium mixed crystal according to claim 1, characterized in that: The z value is 0.05%-20%.
5. The lutetium oxide yttrium silicate lutetium mixed crystal according to claim 1, characterized in that: M a It is a combination of one or more of Ca, Mg, In, Sc and Al.
6. At least one element of Ca, Mg, In, Sc or Al according to claim 5, characterized in that: M a The a value is 0.02%-0.6%.
7. The method for preparing the lutetium oxide yttrium silicate lutetium mixed crystal according to any one of claims 1 to 6, characterized in that: Including the following steps: Step S10: taking dried lutetium oxide, yttrium oxide, cerium oxide, silicon dioxide and an additive containing one or more of Ca, Mg, In, Sc or Al, mixing them evenly according to the mixing ratio, pressing them into a cake shape, and pre-sintering them; obtaining a sintered block material and entering step S20; Step S20: putting the sintered block material in step S10 into an iridium crucible, and then into a pulling furnace; Go to step S30; Step S30: After the seed crystal is installed on the lifting rod, the furnace is sealed and evacuated, and then filled with inert gas, the temperature is increased to melt the sintered block, and the temperature is maintained at a constant temperature, and then step S40 is entered; Step S40: using a seed crystal to seed the crystal, and using a Czochralski growth process to control the pulling speed and crystal rotation speed; after the crystal growth is completed, slowly cooling down and taking out the crystal.
8. The method for preparing the lutetium oxide yttrium silicate lutetium mixed crystal according to claim 8, characterized in that: The seed crystals in step S40 are lutetium oxide and Ce. 2y :Lu 2(1-y-z)-a Y 2z M a Seed crystals made from mixed crystals of SiO5.
9. The method for preparing the lutetium oxide yttrium silicate lutetium mixed crystal according to claim 8, characterized in that: The step S10 is based on the molar ratio (Lu2O3) x :Ce 2y :Lu 2(1-y-z)-a Y 2z M a SiO5=x:1, weigh dry raw materials with a purity higher than 99.99%, mix them evenly, and in the step S10, press the evenly mixed raw materials into cylindrical cakes under a pressure of 100 MPa; pre-sinter at a temperature of 1450° C. for 12 hours; After the seed crystal is installed on the lifting rod in step S30, the furnace is sealed and evacuated to 6×10 -3 After Pa, high-purity argon gas is filled in; In step S40, lutetium oxide and Ce are used. 2y :Lu 2(1-y-z)-a Y 2z M a SiO5 mixed crystal seed inoculation, control the pulling speed to 0.01-5 mm / hour, and the crystal rotation speed to 3-20 rpm.